(untitled) (Research, Society and Development, 2021)
This article was elaborated with the purpose of understanding, in a historical and current context, the participation of women in the maintenance of textile handicraft activities. For this purpose, this research is characterized by a qualitative approach, of a descriptive-exploratory type, based on bibliographic data. The theoretical framework of the research is constituted by authors who establish their discussions around the work category and who present the existing duality in the insertion of the female contingent in the field of work. In addition, authors who analyze domestic handicraft production in the daily life of women in a social and economic perspective and help in the understanding of the historical context related to women’s work, essentially with handicraft, pointing out the possibilities of empowerment of their work through the insertion of craftswomen in solidarity economy entities. In relation to the main results, it is highlighted that women have always worked and that handicrafts have been present in their daily lives for a long time, either because it is a task that had been assigned to them - through a social construction that gave women a reproductive function and maintenance of the domestic space - or because it is an option to acquire income. Crafts made by women in their homes make them face difficult situations through the articulation of paid work and the maintenance of the domestic space, being the insertion of craftswomen in solidarity economy entities, understood as a way to help the work of these women.